Jakuba Sobieskiego opisanie wyprawy na Moskwę (na podstawie "Diariusza ekspedycyjej moskiewskiej dwuletniej królewica Władysława Anno Domini 1617") - Borek, Piotr (My University, 2013)
The essay discusses Jakub Sobieski’s diaries and memories, which belong to the finest specimens of such writing in Polish Baroque. The diary and memoirs of the Moscow campaign of 1617-1618 have survived in only a few copies, with the most important ones in Biblioteka Czartoryskich in Cracow. Reconstruction of Prince Władysław’s struggle for the Russian crown is mostly based on a handwritten testimony called "Diariusz ekspedycyjej moskiewskiej dwuletniej królewica Władysława A. D. 1617" [The Diary of the Two-Year Moscow Campaign by Royal Prince Władysław in 1617]. The events described in the diary span from April 5th, 1617 to December 28th, 1618. The author has arranged the material chronologically, focusing on the text as historical evidence. The conclusion of the text, where Sobieski quotes a fragment of Tacitus’s Annals, points out to the argumentative function of the work, which was supposed to explain to Poles (the king, the sejm and senate, the nobility) that commissaries were right in signing the Truce of Deulino, regarding the safety of the homeland threatened by Turks and Tatars, and the budgetary difficulties of the Crown and Lithuania. The second work by Sobieski is more of a Baroque memoir, composed as a temporal sequence (some fragments have the structure of diary). The author reconstructs the events of the Moscow campaign, beginning with the death of tsar Ivan the Terrible (1584), and leads the narrative to the end of 1618, when the Truce of Deulino. The work is characterized by greater coherence in presentation of facts, their selection, and a more general point of view, pointing out to the failure of Polish dynastic policy. Sobieski seems to be critical of the Polish intervention and the Polish "raison d’état" in this respect. He is also critical of the young prince’s campaign of 1617-1618; he was a commissioner for treaties with Moscow during the campaign.
Jakub Sobieski’s Description of the Moscow Campaign (based on the "Diariusz ekspedycyjej moskiewskiej dwuletniej królewica Władysława Anno Domini 1617" [The Diary of the Two-Year Moscow Campaign by Royal Prince Władysław in 1617])
Keywords: Jakub Sobieski; memoir; diary; war; Polish intervention in Russia during the Time of Troubles